By-Laws, Rules and Regulations : 66th Issue. (By Laws, Rules and Regulations; By Laws, Rules and Regulations ;, 2022)
This volume sets out the IMF's By-Laws, which are adopted under the authority of, and are intended to be complementary to, the IMF's Articles of Agreement, which are considered to prevail in the event of any conflict. The By-Laws cover a number of topics, including the size and composition of the IMF's Board of Governors and Executive Board, applications for IMF membership, IMF quotas, voting rights, staff regulations, and the IMF's Special Drawing Rights.